UPAYA PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM MENDAPATKAN PIALA ADIPURA TAHUN 2017 - Fahrul Rozi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Adipura Cup is an award for the cleanest and most beautiful city / district. With certain criteria, a team formed by the Ministry of Environment and Forestry assesses the cleanliness of the city and its beauty. Kuantan Singingi Regency is one of the regencies that received the Adipura trophy in 2017. This success cannot be separated from the cooperation and coordination of various parties, the institutions that participated in the success of the program. The formulation of the problem of this research is what are the efforts of the Kuantan Singingi Regency Government in getting the Adipura trophy in 2017? This research is descriptive research with a qualitative approach. The location of this study was conducted in Kuantan Singingi Regency. Data collection techniques are carried out with qualitative data analysis. While the results of the study concluded that the efforts of the Regional Government of Kuantan Singingi Regency in obtaining the Adipura trophy were already optimal. Judging from the four coordination indicators, there are two indicators which are not optimal in their implementation, namely communication and meeting meetings. In addition, on the task division indicator and cooperation has been running optimally and no significant problems were found. While the factors that influence the efforts of the Regional Government of Kuantan Singingi Regency in obtaining Adipura trophies there are supporting factors, namely the high commitment of the regional head and the existence of funds. While the inhibiting factor is the lack of public awareness of the environment. Keywords: Efforts, Local Government, Adipura Cup